Characteristics of Wet and Dried Distillers Grains on Ruminal Fermentation and Effects of Dietary Wet Distillers Grains on Performance of Hanwoo Steers - Ill Young Kim; Gyu Chul Ahn; Hyung Jun Kwak; Yoo Kyung Lee; Young Kyoon Oh; Sang Suk Lee; Jeong Hoon Kim; Keun Kyu Park (Asian-Australasian Journal of Animal Sciences, 2015)
Two experiments were conducted to evaluate the nutrient composition, in vitro dry matter disappearance (IVDMD) and organic matter disappearance (IVOMD) of three kinds of distillers grains (DG); i) wet distillers grains (WDG, KRW 25/kg), ii) dried distillers grains (DDG, KRW 280/kg), iii) dried distillers grains with solubles (DDGS, KRW 270/kg) produced from tapioca 70% and rice 30%, and to evaluate dietary effects of WDG on the performance of Hanwoo steers. In Exp. 1, twelve-WDG, four-DDG and one-DDGS were collected from seven ethanol plants. Average crude protein, crude fiber, neutral detergent fiber, and acid detergent fiber of WDG, DDG, and DDGS were: 32.6%, 17.8%, 57.5%, and 30.2% for WDG, 36.7%, 13.9%, 51.4%, and 30.5% for DDG, and 31.0%, 11.9%, 40.3%, and 21.2% for DDGS (DM basis), respectively. The DDGS had a higher quantity of water-soluble fraction than WDG and DDG and showed the highest IVDMD (p<0.05) in comparison to others during the whole experimental time. The IVDMD at 0 to 12 h incubation were higher (p<0.05) in DDG than WDG, but did not show significant differences from 24 to 72 h. The same tendency was observed in IVOMD, showing that DG made from tapioca and rice (7:3) can be used as a feed ingredient for ruminants. Considering the price, WDG is a more useful feed ingredient than DDG and DDGS. In Exp. 2, 36 Hanwoo steers of 21 months (495.1±91 kg) were randomly assigned to one of three dietary treatments for 85 days; i) Control (total mixed ration, TMR), ii) WDG 10% (TMR containing 10% of WDG, as fed basis), and iii) WDG 20% (TMR containing 20% of WDG, as fed basis). With respect to body weight and average daily gain, there were no differences between control and WDG treatments during the whole experimental period. Dry matter intake of control (9.34 kg), WDG 10% (9.21 kg) and 20% (8.86 kg) and feed conversion ratio of control (13.0), WDG 10% (13.2) and 20% (12.1) did not show differences between control and WDG treatments. Thus, the use of WDG up to 20% in TMR did not show any negative effect on the performance of Hanwoo steers.